Окремі сторінки історії і сьогодення діяльності Інституту геотехнічної механіки ім. М.С. Полякова НАН України - Булат, А.Ф. (Геотехническая механика, 2012)
В статье приведены сведения об основных этапах работы отделов Института геотехнической механики за его пятидесятилетнюю историю, ведущих ученых института, научных открытиях и полученных Государственных и научных премиях. The article shows the key stages of work of departments of the Institute of Geotechnical Mechanics during its 50-year history and represents the Institute’s leading scientists, scientific discoveries and numerous government and scientific awards received by the Institute.